Factors influencing classroom participation of undergraduate nursing students - Abeasi, Doreen Asantewa; Kwakwa, Paul Adjei (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2020)
Participation is very essential for achieving positive learning outcomes in students especially for nursing students who by the nature of the career are required to be critical thinkers, problem solvers and very analytic. The study sought to examine the factors influencing classroom participation among 100 undergraduate nursing students of the Presbyterian University College, Ghana (PUCG). The findings of the study revealed that main student factors influencing participation in the classroom were being shy, lack of control over English language and inadequate preparation. The desire to remain anonymous did not influence participation. Adequate wait time, mentioning of students’ name, offering of equal opportunities to students and awarding marks to students were faculty factors identified to influence students to participate in class. It was found that the gender of the lecturer did not affect participation. Also, the most important classroom climate factor mentioned to influence participation was large class size. It is recommended among many that lecturers should set expectations for students’ participation and counselling should be done for students who are shy in order to boast their self-confidence which is likely to improve classroom participation.